2014
DOI: 10.1089/acm.2014.5219.abstract
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Acupuncture on Heart Rate Variability: A Systematic Review

Abstract: Aim. To summarize all relevant trials and critically evaluate the effect of acupuncture on heart rate variability (HRV). Method. This was a systematic review with meta-analysis. Keyword search was conducted in 7 databases for randomized controlled trials (RCTs). Data extraction and risk of bias were done. Results. Fourteen included studies showed a decreasing effect of acupuncture on low frequency (LF) and low frequency to high frequency ratio (LF/HF ratio) of HRV for nonhealthy subjects and on normalized low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
(66 reference statements)
0
5
0
Order By: Relevance
“…HRV biofeedback has shown some positive effects upon HRV (Prinsloo et al, 2014; Wheat and Larkin 2010), but the evidence is still limited. Acupuncture (Chung et al, 2014) has been employed with some encouraging but limited results, while the benefits of Yoga remain uncertain (Posadzki et al, 2015). Mindfulness may also enhance HRV, but this remains uncertain (Nijjar et al, 2014).…”
Section: Therapeutic Interventions To Enhance Hrvmentioning
confidence: 99%
“…HRV biofeedback has shown some positive effects upon HRV (Prinsloo et al, 2014; Wheat and Larkin 2010), but the evidence is still limited. Acupuncture (Chung et al, 2014) has been employed with some encouraging but limited results, while the benefits of Yoga remain uncertain (Posadzki et al, 2015). Mindfulness may also enhance HRV, but this remains uncertain (Nijjar et al, 2014).…”
Section: Therapeutic Interventions To Enhance Hrvmentioning
confidence: 99%
“…At the same time, HCPs not expressing ESKs may benefit more from modalities such as acupuncture, which may be accompanied by pain and discomfort, if only minor. In a systematic review, acupuncture was shown to decrease both LF and LF/HF ratios (43).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical studies have illustrated that acupuncture of Neiguan spot has been shown to lessen nausea and vomiting which are related to vagal modulation, acupuncture of Neiguan spot could be a vagal enhancer in healthy subjects [11]. Joanne W. Y. Chung's meta-analysis [12] supported the possible role of acupuncture on modulating the autonomic she found that LF, HF and LF/HF ratio of HRV significantly decreased. Tatsuo et al [13] demonstrated that acupuncture on Neiguan spot reduced cardiac excitability and corrected the imbalance between cardiac sympathetic and vagal nerve activity during left stellate ganglion (LSG) stimulation in Yorkshire pigs.…”
Section: Opinionmentioning
confidence: 98%